X‐ray free‐electron laser wavefront sensing using the fractional Talbot effect. (12th February 2020) - Liu, Yanwei; Seaberg, Matthew; Feng, Yiping; Li, Kenan; Ding, Yuantao; Marcus, Gabriel; Fritz, David; Shi, Xianbo; Grizolli, Walan; Assoufid, Lahsen; Walter, Peter; Sakdinawat, Anne
Abstract : A wavefront sensor for an X‐ray free‐electron laser has been developed using the fractional Talbot effect. This wavefront sensor enables measurements over a wide range of energies, as is common on X‐ray instruments, and is compatible with the high average power pulses expected in upcoming X‐ray free‐electron laser upgrades. Abstract : Wavefront sensing at X‐ray free‐electron lasers is important for quantitatively understanding the fundamental properties of the laser, for aligning X‐ray instruments and for conducting scientific experimental analysis. A fractional Talbot wavefront sensor has been developed. This wavefront sensor enables measurements over a wide range of energies, as is common on X‐ray instruments, with simplified mechanical requirements and is compatible with the high average power pulses expected in upcoming X‐ray free‐electron laser upgrades. Single‐shot measurements were performed at 500 eV, 1000 eV and 1500 eV at the Linac Coherent Light Source. These measurements were applied to study both mirror alignment and the effects of undulator tapering schemes on source properties. The beamline focal plane position was tracked to an uncertainty of 0.12 mm, and the source location for various undulator tapering schemes to an uncertainty of 1 m, demonstrating excellent sensitivity. These findings pave the way to use the fractional Talbot wavefront sensor as a routine, robust and sensitive tool at X‐ray free‐electron lasers as well as other high‐brightness X‐ray sources.